Evaluasi Usability & Rekomendasi Perbaikan Desain Antarmuka Sistem Self-Service dalam Penyelesaian Kendala Pelanggan E-commerce - Agri Fina; Santoso, Harry Budi (The Indonesian Journal of Computer Science, 2024)
Self-service has been widely adopted by various companies worldwide for different purposes; for example, in customer service settings, it automates repetitive and simpler tasks handled by agents. However, self-service systems for resolving customer issues have limitations. This study thus aims to evaluate the usability of the self-service system on the help center of an e-commerce app. Usability evaluation was conducted using both qualitative and quantitative methods. Quantitative data were collected through a survey with demographic and introductory questions, the System Usability Scale (SUS) questionnaire, and follow-up questions. In total, 200 responses were collected (195 of which were valid). Since the average SUS score was 67.35, the data analysis revealed that the self-service system has usability issues, particularly in learnability and efficiency. Additionally, usability testing and in-depth interviews were conducted with 12 participants to collect qualitative data to be analyzed using thematic analysis. Based on these findings, the study concludes that the development team can prepare a plan to enhance the user interface of the self-service system on E-Commerce XYZ’s help center to enhance usability.